Development of Information Systems for Human Resources (HR), Cooperation, Facilities and Infrastructure to Support Accreditation of Study Program at Postgraduate Universitas Negeri Semarang - Susyanto, Tugiman; Wijayanti, Hermin; Supriyadi, Supriyadi; Septiawan, Meldy; Budiyanto, Budiyanto (Journal of Research and Educational Research Evaluation, 2022)
Postgraduate Universitas Negeri Semarang as an educational institution organized by the government is required to improve the quality of services, be able to set service standards with the dimensions of maintaining quality and meeting the needs of the entire academic community both in Postgraduate and the scope of UNNES. Service quality is also intended so that all stakeholders can enjoy the service to the fullest. Therefore, to facilitate the use of services that integrate several aspects, such as human resources (HR), cooperation, facilities and infrastructure, the Postgraduate Program seeks to develop an online information system that is expected to facilitate the performance of the UNNES academic community. Based on the explanation above, UNNES Postgraduate wants to develop an information system that includes human resources (HR), cooperation and facilities and infrastructure. The collection of data in these 3 fields is very important so that it can be used when data is needed during accreditation. The conclusion is the Postgraduate Accreditation Information System (SIAPA) can be used by the UNNES Postgraduate academic community, especially for administration in the field of human resources (HR), cooperation, facilities and infrastructure.